Electroacupuncture plus moxibustion for major depressive disorder: A randomized, sham-controlled, pilot clinical trial - Mikyung Kim; Eun-Ji Choi; O-Jin Kwon; Hyo-Ju Park; Ae-Ran Kim; Bok-Nam Seo; Sun-Yong Chung; Jun-Hwan Lee; Joo-Hee Kim (Integrative Medicine Research)
Background: The first treatment option for major depressive disorder (MDD) is antidepressants, however, there is substantial demand for alternative therapies due to its low compliance and remission rates. This study was aimed to explore the effectiveness, safety, and feasibility of electroacupuncture plus moxibustion therapy for MDD. Methods: Thirty adults with MDD were randomly assigned to the treatment group (TG) or control group (CG). The TG was treated with electroacupuncture plus moxibustion, and the CG received sham interventions at non-acupoints for 8 weeks. The primary outcome measure was the intergroup difference of the mean change of total score of the Hamilton rating scale for depression (HRSD) between baseline and week 9. Secondary outcome measures were Beck's depression inventory, insomnia severity index, the state-trait anxiety inventory, the EuroQol-5 dimension index, the measure yourself medical outcome profile version 2, and frontal alpha asymmetry measured by electroencephalography. Adverse events (AEs) were monitored for safety assessment. Results: The primary outcome measure was not significantly different between the two groups (p=0.2641), although the scores of HRSD in both groups improved significantly after treatment. No significant difference was identified between groups in secondary outcome measures. The incidence of AE was not significantly different between the two groups (p=0.1067). Conclusion: A clinical trial using electroacupuncture plus moxibustion for MDD seems feasible. However, further studies with the larger size, adopting ideal controls are warranted to provide a confirmative conclusion to the efficacy and safety of electroacupuncture plus moxibustion for MDD. Trial registration: The protocol was registered at Korean Clinical Trial Registry (CRIS-KCT0001810)